전위 - pH 도표를 이용한 금속 나노입자 형성 - 이규환(Kyu Hwan Lee) (Biuletyn Uniejowski, 2017)
This article introduces how to use potential-pH diagram for the formation of metallic nanoparticles, based upon the data obtained from the experiments. It is important to measure the values of equilibrium potentials of the reactions for the use of potential-pH diagram in aqueous and non-aqueous solutions. This article includes how to obtain the potential-pH diagrams in solutions containing particles and in non-aqueous solutions. 본 기술해설은 일본의 표면 처리 학술지인 표면기술(表面技術) (2013년, 64권 2호)에 게재된 'Eh-pH 도표의 표면기술에의 응용'이라는 제하의 총 6편의 논문으로 구성된 소특집 중 두 번째인 '전위-pH 도표를 이용한 금속 나노입자 형성 프로세스 구축' 논문을 소개한 것으로서, 원문을 읽고 싶다면 표면기술(表面技術)을 참조하길 바란다.